HEALTH SERVICES RESEARCH IN PUBLIC HEALTH ENCOMPASSES A BROAD RANGE OF STUDIES THAT AIM TO IMPROVE HEALTHCARE ACCESS, QUALITY, EQUITY, AND EFFICIENCY - Nouf Abdulfattah Abdulrahman Hajeb, Mazhar Salem Mohammed Balobaid, Nada Khaled Fahad Al-Obaid, Nawaf Abdulaziz Alanazi, Basheir Bandar bin Jamaan, (Chelonian Research Foundation, 2023)
Health services research in public health is a crucial aspect of healthcare that focuses on improving healthcare access, quality, and equity for all individuals. This essay explores the various studies within health services research at the Master level, highlighting the methodologies used, results obtained, and discussions surrounding the topic. By analyzing different aspects of health services research in public health, this essay aims to shed light on the importance of such studies in advancing healthcare systems worldwide.